Preparation method of high-conductivity PEDOT conductive powder
By using a mixed solvent of anhydrous ethanol and water in the preparation of PEDOT powder for solution polymerization, combined with ferric chloride as an oxidant, reaction at room temperature, complex process, high energy consumption and unstable conductivity in the prior art are solved. The problem of this is that PEDOT powder preparation with high conductivity and high stability is achieved.
Patent Information
- Application Number
- CN202411520534.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-29
AI Technical Summary
The existing PEDOT powder preparation process is complex, has high energy consumption, unstable conductivity, and has impurities problems, which affects product quality.
A high conductivity PEDOT powder was prepared by solution polymerization using a mixed solvent of anhydrous ethanol and water. Ferric chloride was used as an oxidizing agent and reacted at room temperature to avoid the introduction of impurities caused by the addition of dispersant in suspension polymerization.
It has achieved the preparation of high conductivity PEDOT powder, with a conductivity of 100S/cm, with simple process, low energy consumption, high product stability, and suitable for large-scale production.
Smart Images

Figure CN119390950A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of conductive polymers, and more specifically, relates to a method for preparing high-conductivity PEDOT conductive powder. Background Art
[0002] After more than 40 years of development, people have conducted in-depth research on conductive polymers, and a variety of conductive materials have been introduced and have been widely used in display materials, batteries, conductive materials, biomedical materials, sensors, electromagnetic protection and other fields. Among these materials, PEDOT has become a popular product among conductive polymers due to its high conductivity, high stability, low toxicity and environmental friendliness. It has a simple preparation process, a wide range of applications and high practicality.
[0003] The current PEDOT products are mainly PEDOT:PSS conductive inks, which are mostly used to form films by brushing, spraying, dipping, etc. Compared with conductive inks, powders have a wider range of applications. In addition to reconfiguring powders into inks, they can also be directly added as fillers to paints and coatings to enhance the antistatic ability of the material. In addition, the storage method of powders is relatively simple and more stable, and its commercial significance is significantly greater than that of conductive inks.
[0004] At present, the preparation process of PEDOT powder is mainly based on suspension precipitation polymerization. During the reaction process, continuous heating and stirring are required and the temperature control is relatively strict, which leads to high energy consumption in the production process and low conductivity of the produced PEDOT powder. At the same time, the water-based suspension polymerization reaction is fast and the conductivity is difficult to control, resulting in unstable conductivity of the product. In addition, the current industrial production of PEDOT still has problems such as the use of a large number of raw materials, small production scale, complex production methods / environmentally unfriendly.
[0005] In the currently commercialized PEDOT:PSS, since PSS itself is not conductive, the addition of a large amount of PSS acts as an insulating barrier to PEDOT, greatly reducing the conductivity of the PEDOT product. In other existing literature, PEDOT powder with high conductivity was prepared by suspension polymerization by introducing dispersants such as sodium dodecyl sulfate. However, these active agents are extremely difficult to clean, and greatly increase the difficulty and cost of the PEDOT product cleaning process. In addition, these impurities are difficult to remove completely, which has an adverse effect on the quality of the PEDOT product and its subsequent practical use. Therefore, there is an urgent need to provide a method for preparing a high-conductivity PEDOT conductive powder with low energy consumption, few impurities, and simple process. Summary of the invention
[0006] In view of the defects of the prior art, the purpose of the present invention is to provide a method for preparing high-conductivity PEDOT powder, aiming to solve the technical problems of the prior art such as complex preparation process and introduction of impurities of high-conductivity PEDOT powder.
[0007] To achieve the above object, the present invention provides a method for preparing a high-conductivity PEDOT conductive powder, comprising the following steps:
[0008] (1) dissolving 3,4-ethylenedioxythiophene monomer in anhydrous ethanol to obtain an EDOT solution;
[0009] (2) dissolving an oxidant, ferric chloride, in water to obtain a ferric chloride solution;
[0010] (3) mixing the EDOT solution and the ferric chloride solution to obtain a mixed solution, wherein the volume ratio of anhydrous ethanol to water in the mixed solution is (1-2):1;
[0011] (4) The mixed solution of step (3) is continuously stirred for several days to allow a polymerization reaction to occur. After the reaction is completed, the solid-liquid separation is performed, and the obtained solid phase product is washed and dried to obtain a high-conductivity PEDOT conductive powder.
[0012] Preferably, the mass percentage concentration of 3,4-ethylenedioxythiophene monomer in the EDOT solution in step (1) is 3-8wt%.
[0013] Preferably, the molar ratio of the 3,4-ethylenedioxythiophene monomer in step (1) to the oxidant ferric chloride in step (2) is 1:6-10.
[0014] Preferably, the volume ratio of anhydrous ethanol to water in the mixed solution of step (3) is (1.2-1.8):1.
[0015] Preferably, in step (3), the ferric chloride solution is added to the EDOT solution all at once, or the ferric chloride solution is added dropwise to the EDOT solution.
[0016] Preferably, in step (4), the mixed solution is continuously stirred at 20-30° C. for 3-9 days.
[0017] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:
[0018] (1) The present invention proposes to use a mixed solvent of anhydrous ethanol and water in a specific ratio to prepare high-conductivity PEDOT powder by solution polymerization, transforming the traditional suspension polymerization method into a solution polymerization method, using ferric chloride solution as an oxidant, and controlling the reaction time at room temperature without adding any other additives to achieve the preparation of high-conductivity PEDOT powder.
[0019] (2) The present invention uses ethanol as the EDOT monomer solvent, controls the alcohol-water volume ratio of the total solvent in the reaction system, can dissolve the EDOT monomer and ferric chloride in the same phase for reaction, and transforms the suspension precipitation polymerization process commonly used in the preparation of PEDOT powder into solution precipitation polymerization, which solves the problem of impurity introduction caused by adding a dispersant in suspension polymerization, and the reaction is easy to control, the generated particles are finer, and it is easier to obtain a conductive powder with high conductivity. The reaction is carried out at room temperature without the need to accurately control the reaction temperature, which can greatly save energy and reduce production expenses. This method has a simple process flow, low energy consumption, simple operation, fewer types of raw materials, fewer toxic and harmful substances in the raw materials, and low environmental hazards, and is suitable for large-scale production.
[0020] (3) The present invention can stably prepare a product with an electrical conductivity of 10 by adjusting the polymerization process parameters. 0 PEDOT powder with a S / cm order of magnitude. It should be noted that compared with the suspension polymerization method using water as the solvent, the yield of PEDOT powder did not decrease significantly, the conductivity was stable and controllable, and other properties of the powder were not significantly affected. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Reaction route for PEDOT polymerization;
[0022] Figure 2 is a process flow chart of the preparation method of the present invention;
[0023] Figure 3 This is the PEDOT powder prepared by the present invention. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0025] The embodiments of the present invention are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and processes are given, but the protection scope of the present invention is not limited to the following embodiments. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.
[0026] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0027] The present invention provides a high conductivity PEDOT conductive powder (conductivity is 10 0 S / cm order of magnitude), comprising the following steps:
[0028] (1) dissolving 3,4-ethylenedioxythiophene monomer (abbreviated as EDOT) in anhydrous ethanol to obtain an EDOT solution;
[0029] (2) dissolving an oxidant, ferric chloride, in water to obtain a ferric chloride solution;
[0030] (3) mixing the EDOT solution and the ferric chloride solution to obtain a mixed solution, wherein the volume ratio of anhydrous ethanol to water in the mixed solution is (1-2):1, preferably (1.2-1.8):1;
[0031] (4) The mixed solution in step (3) is continuously stirred for several days without adding any other additives to allow a polymerization reaction to occur. After the reaction is completed, the solid and liquid are separated, and the obtained solid phase product is washed and dried to obtain a high-conductivity PEDOT conductive powder. The reaction route is shown in FIG. Figure 1 shown.
[0032] In some embodiments, the molar ratio of the 3,4-ethylenedioxythiophene monomer in step (1) to the oxidant ferric chloride in step (2) is 1:6-10. The mass percentage concentration of the 3,4-ethylenedioxythiophene monomer in the EDOT solution in step (1) is 3-8wt%.
[0033] In some embodiments, in step (3), the ferric chloride solution is added to the EDOT solution all at once, or the ferric chloride solution is added dropwise to the EDOT solution.
[0034] In a preferred embodiment, in step (2), the ferric chloride solution is added dropwise to the EDOT solution, and the adding time is generally controlled within 2 hours, and the addition is performed at a uniform speed as much as possible to improve the reaction uniformity.
[0035] In some embodiments, the ferric chloride is ferric chloride hexahydrate or anhydrous ferric chloride.
[0036] In some embodiments, in step (4), the mixed solution is continuously stirred at 20-30° C. for 3-9 days. The stirring is mechanical stirring or magnetic stirring. In step (4), the solid product obtained by solid-liquid separation is alternately washed in dilute hydrochloric acid (such as 1M hydrochloric acid), water and ethanol. In step (4), the drying is vacuum drying at 70-90° C. for 36-72 hours.
[0037] In some embodiments, the water described in the present invention is one or more of ultrapure water, deionized water, double distilled water, pure water, and distilled water.
[0038] In view of the many shortcomings of the traditional PEDOT:PSS preparation method and the water-based precipitation polymerization method for preparing PEDOT powder, such as many impurities, high production energy consumption (heating is required), complex production process, and low conductivity, the present invention provides a controllable preparation method of PEDOT solution precipitation polymerization, aiming to ensure that by adjusting the process parameters, a PEDOT powder with high conductivity (conductivity between 10 0 S / cm order of magnitude) and ensure a good yield. The PEDOT powder ethanol-water mixed solvent solution precipitation polymerization method described in the present invention can achieve the preparation of high conductivity PEDOT powder without additional temperature control. This method is simple to operate, has a small number of raw materials, saves energy, and has good repeatability. The PEDOT product has stable performance and high conductivity, which has practical commercial significance for industrial mass production.
[0039] In some embodiments, such as Figure 2 As shown, the specific steps include:
[0040] S1. Dissolution of EDOT: A certain amount of ethanol is added to a reaction container and EDOT monomer is added, and the EDOT monomer is fully dissolved by continuous stirring to obtain a clear and transparent light yellow EDOT ethanol solution.
[0041] S2, adding oxidant ferric chloride hexahydrate solution: take a certain amount of ferric chloride hexahydrate and dissolve it in water. The amount of water needs to be calculated so that the ethanol used in S1 and the water contained in this step meet a certain volume ratio. Keep stirring in the reaction vessel and add the ferric chloride solution to the reaction vessel.
[0042] S3. Polymerization of EDOT: Keep stirring and allow the reaction to continue for several days.
[0043] S4. Collection, washing and drying of PEDOT: After the reaction is completed, use filtration to separate the reaction liquid from the solid and liquid, leaving a solid product. Then, fully disperse the solid product in 1M hydrochloric acid, and wash the PEDOT solid by ultrasonic heating cleaning. Set the temperature to 80°C each time, and use ultrasound for 30 minutes. After the ultrasonic cleaning is completed, use filtration to separate the PEDOT solid product, and repeat the cleaning several times. After the hydrochloric acid washing is completed, use water to wash several times in the same way, put the solid product into a vacuum drying oven, set it to 80°C and vacuum dry it for 48 hours to obtain PEDOT powder.
[0044] The present invention provides a method for preparing a high-conductivity PEDOT conductive powder with low energy consumption, few impurities and simple process. EDOT can be dissolved in ethanol, and ferric chloride can be dissolved in ethanol and water at the same time. Therefore, by using an ethanol-water mixed solvent, the polymerization mode can be changed from suspension polymerization to solution polymerization. Ethanol, as an EDOT polymerization inhibitor, can slow down the polymerization rate of EDOT, and reacting at room temperature can further make the EDOT polymerization rate slow and stable. Due to the slow polymerization rate, the influence of temperature fluctuation on the EDOT polymerization rate can be reduced at the same time, so that PEDOT powder with stable conductivity can be obtained. In addition, since PSS is not added, the anions in the reaction system are chloride ions, so the problem of insulation barrier is improved.
[0045] The present invention uses an alcohol-water mixed solvent to replace the water solvent in the traditional preparation process, transforms the suspension polymerization process into a solution polymerization process, and obtains PEDOT powder with excellent performance without adding any additives. The method has the characteristics of high efficiency and energy saving. Under room temperature conditions, by controlling the proportion of reaction raw materials and reaction time, a PEDOT powder with high conductivity is obtained. At the same time, the product of the preparation process is stable and has high repeatability. Compared with the mainstream PEDOT products currently on the market, the PEDOT powder product has higher conductivity and processability.
[0046] The following are specific embodiments:
[0047] Example 1
[0048] S1. Dissolution of EDOT: 150 mL of anhydrous ethanol and 5 g of EDOT were added to a conical flask, and a magnetic stirrer was added to the conical flask. The conical flask was then placed in a magnetic stirrer under a room temperature water bath and stirred for 30 minutes to obtain a completely dissolved EDOT ethanol solution.
[0049] S2, the dropping of ferric chloride: take 76.1g ferric chloride hexahydrate (8 times the mole number of EDOT, containing 30.4mL water) and add 49.6mL distilled water, ultrasonic dispersion makes ferric chloride hexahydrate completely dissolved.The ferric chloride hexahydrate solution of configuration is moved to a constant pressure funnel, and the ferric chloride hexahydrate solution is slowly added dropwise to EDOT-ethanol solution, and the dropping time is not less than 2 hours.After completion of dropwise addition, 20mL distilled water is used to clean glassware, and cleaning solution is added to the reaction solution in a lump (now containing 100mL water, 150mL anhydrous ethanol in the system).
[0050] S3. Polymerization of EDOT: Keep stirring continuously and react for 7 days at a reaction temperature of 20-30°C.
[0051] S4. Collection, washing and drying of PEDOT: After the reaction is completed, use a G6 sand core funnel to filter the reaction solution to obtain a blue-black PEDOT solid. Transfer the PEDOT solid to a 500mL beaker and add 200mL of 1M hydrochloric acid. Set the ultrasonic time to 3h and the ultrasonic temperature to 80°C to disperse the PEDOT solid in 1M hydrochloric acid. After ultrasound, use a sand core funnel to filter and separate the solid product. Continue ultrasonic washing with 1M hydrochloric acid in this way, and wash for 30 minutes each time, for a total of 6 times. Then change to distilled water, follow this method to ultrasonically disperse and wash 6 times, then put it in a vacuum drying oven, set the drying temperature to 80°C and dry for 48 hours. The appearance of the PEDOT solid product after drying is as follows Figure 3 The obtained PEDOT solid product was put into an agate mill and crushed into fine powder, thus obtaining PEDOT powder.
[0052] Prepared PEDOT powder test:
[0053] 1. PEDOT conductivity test method: Pour a certain amount of PEDOT powder into a tableting mold, pressurize to 40mPa and maintain the pressure for 30 minutes. Then take out the PEDOT sheet, measure its thickness and use a four-probe resistivity tester to test its conductivity (the four-probe tester is Japan Mitsubishi MCP-TP610, the test probe is Japan Mitsubishi MCP-TP06P, and the probe calibrator is Japan Mitsubishi RMH311). The test shows that the conductivity of the PEDOT powder is 7.786×10 0 S / cm, excellent electrical conductivity.
[0054] 2. PEDOT conversion rate test method: The conversion rate calculation formula is as follows
[0055]
[0056] Where: m PEOOT is the mass of the collected product; m EDOTis the mass of the added EDOT monomer. After drying, the PEDOT solid was collected, and the conversion rate of PEDOT was calculated according to this formula to be 70.4%, which is a high yield.
[0057] Example 2
[0058] S1. Dissolution of EDOT: 150 mL of anhydrous ethanol and 5 g of EDOT were added to a conical flask, and a magnetic stirrer was added to the conical flask. The conical flask was then placed in a magnetic stirrer under a room temperature water bath and stirred for 30 minutes to obtain a completely dissolved EDOT ethanol solution.
[0059] S2, the dropping of ferric chloride: take 76.1g ferric chloride hexahydrate (8 times the mole number of EDOT, containing 30.4mL water) and add 49.6mL distilled water, ultrasonic dispersion makes ferric chloride hexahydrate completely dissolved.The ferric chloride hexahydrate solution of configuration is moved to a constant pressure funnel, and the ferric chloride hexahydrate solution is slowly added dropwise to EDOT-ethanol solution, and the dropping time is not less than 2 hours.After completion of dropwise addition, 20mL distilled water is used to clean glassware, and cleaning solution is added to the reaction solution in a lump (now containing 100mL water, 150mL anhydrous ethanol in the system).
[0060] S3. Polymerization of EDOT: Keep stirring continuously and react for 5 days at a reaction temperature of 20-30°C.
[0061] S4. Collection, washing and drying of PEDOT: After the reaction is completed, use a G6 sand core funnel to filter the reaction solution to obtain a blue-black PEDOT solid. Transfer the PEDOT solid to a 500mL beaker and add 200mL of 1M hydrochloric acid. Set the ultrasonic time to 3h and the ultrasonic temperature to 80℃ to disperse the PEDOT solid in 1M hydrochloric acid. After ultrasound, filter and separate the solid product with a sand core funnel. Continue ultrasonic washing with 1M hydrochloric acid in this way, and wash for 30min each time, for a total of 6 times. Then change to distilled water, ultrasonically disperse and wash 6 times in this way, put it in a vacuum drying oven, set the drying temperature to 80℃ and dry for 48h. Put the obtained PEDOT solid product into an agate mill and grind it into fine powder to obtain PEDOT powder.
[0062] Test of prepared PEDOT powder: The test method of PEDOT powder is the same as that of Example 1. The conductivity of the PEDOT powder was measured to be 7.006×10 0 S / cm, and the conversion rate was 55.6%.
[0063] Example 3
[0064] S1. Dissolution of EDOT: 150 mL of anhydrous ethanol and 5 g of EDOT were added to a conical flask, and a magnetic stirrer was added to the conical flask. The conical flask was then placed in a magnetic stirrer under a room temperature water bath and stirred for 30 minutes to obtain a completely dissolved EDOT ethanol solution.
[0065] S2, the dropping of ferric chloride: take 76.1g ferric chloride hexahydrate (8 times the mole number of EDOT, containing 30.4mL water) and add 49.6mL distilled water, ultrasonic dispersion makes ferric chloride hexahydrate completely dissolved.The ferric chloride hexahydrate solution of configuration is moved to a constant pressure funnel, and the ferric chloride hexahydrate solution is slowly added dropwise to EDOT-ethanol solution, and the dropping time is not less than 2 hours.After completion of dropwise addition, 20mL distilled water is used to clean glassware, and cleaning solution is added to the reaction solution in a lump (now containing 100mL water, 150mL anhydrous ethanol in the system).
[0066] S3. Polymerization of EDOT: Keep stirring continuously and react for 9 days at a reaction temperature of 20-30°C.
[0067] S4. Collection, washing and drying of PEDOT: After the reaction is completed, use a G6 sand core funnel to filter the reaction solution to obtain a blue-black PEDOT solid. Transfer the PEDOT solid to a 500mL beaker and add 200mL of 1M hydrochloric acid. Set the ultrasonic time to 3h and the ultrasonic temperature to 80℃ to disperse the PEDOT solid in 1M hydrochloric acid. After ultrasound, filter and separate the solid product with a sand core funnel. Continue ultrasonic washing with 1M hydrochloric acid in this way, and wash for 30min each time, for a total of 6 times. Then change to distilled water, ultrasonically disperse and wash 6 times in this way, put it in a vacuum drying oven, set the drying temperature to 80℃ and dry for 48h. Put the obtained PEDOT solid product into an agate mill and grind it into fine powder to obtain PEDOT powder.
[0068] Test of prepared PEDOT powder: The test method of PEDOT powder is the same as that of Example 1. The conductivity of the PEDOT powder was measured to be 5.129×10 0 S / cm, and the conversion rate was 76%.
[0069] Example 4
[0070] S1. Dissolution of EDOT: 150 mL of anhydrous ethanol and 5 g of EDOT were added to a conical flask, and a magnetic stirrer was added to the conical flask. The conical flask was then placed in a magnetic stirrer under a room temperature water bath and stirred for 30 minutes to obtain a completely dissolved EDOT ethanol solution.
[0071] S2, the dropping of ferric chloride: take 76.1g ferric chloride hexahydrate (8 times the mole number of EDOT, containing 30.4mL water) and add 49.6mL distilled water, ultrasonic dispersion makes ferric chloride hexahydrate completely dissolved.The ferric chloride hexahydrate solution of configuration is moved to a constant pressure funnel, and the ferric chloride hexahydrate solution is slowly added dropwise to EDOT-ethanol solution, and the dropping time is not less than 2 hours.After completion of dropwise addition, 20mL distilled water is used to clean glassware, and cleaning solution is added to the reaction solution in a lump (now containing 100mL water, 150mL anhydrous ethanol in the system).
[0072] S3. Polymerization of EDOT: Keep stirring continuously and react for 3 days at a reaction temperature of 20-30°C.
[0073] S4. Collection, washing and drying of PEDOT: After the reaction is completed, use a G6 sand core funnel to filter the reaction solution to obtain a blue-black PEDOT solid. Transfer the PEDOT solid to a 500mL beaker and add 200mL of 1M hydrochloric acid. Set the ultrasonic time to 3h and the ultrasonic temperature to 80℃ to disperse the PEDOT solid in 1M hydrochloric acid. After ultrasound, filter and separate the solid product with a sand core funnel. Continue ultrasonic washing with 1M hydrochloric acid in this way, and wash for 30min each time, for a total of 6 times. Then change to distilled water, ultrasonically disperse and wash 6 times in this way, put it in a vacuum drying oven, set the drying temperature to 80℃ and dry for 48h. Put the obtained PEDOT solid product into an agate mill and grind it into fine powder to obtain PEDOT powder.
[0074] Test of prepared PEDOT powder: The test method of PEDOT powder is the same as that of Example 1. The conductivity of the PEDOT powder was measured to be 6.919×10 0 S / cm, and the conversion rate was 37.2%.
[0075] By comparing Example 1, Example 2, Example 3 and Example 4, it can be found that the PEDOT powder prepared by this method has excellent conductivity and can achieve high conversion rate while having high conductivity. Compared with Example 1, Example 2 has little effect on conductivity by reducing the reaction time, but the conversion rate decreases significantly; Example 3 prolongs the reaction time, the conductivity decreases slightly, but the conversion rate can be significantly improved; Example 4 greatly reduces the reaction time, the conductivity is still at the same order of magnitude, but the conversion rate decreases significantly.
[0076] Comparative Example 1
[0077] S1. Dissolution of EDOT: 150 mL of anhydrous ethanol and 5 g of EDOT were added to a conical flask, and a magnetic stirrer was added to the conical flask. The conical flask was then placed in a magnetic stirrer under a room temperature water bath and stirred for 30 minutes to obtain a completely dissolved EDOT ethanol solution.
[0078] S2, the dropping of ferric chloride: take 76.1g ferric chloride hexahydrate (8 times the mole number of EDOT, containing 30.4mL water) and add 49.6mL anhydrous ethanol, ultrasonic dispersion makes ferric chloride hexahydrate completely dissolved.The ferric chloride hexahydrate solution of configuration is moved to a constant pressure funnel, and the ferric chloride hexahydrate solution is slowly added dropwise to EDOT-ethanol solution, and the dropping time is not less than 2 hours.After completion of dropwise addition, 20mL anhydrous ethanol is used to clean glassware, and cleaning solution is added to the reaction solution in a lump (now there are 30.4mL water and 219.6mL anhydrous ethanol in the system).
[0079] S3. Polymerization of EDOT: Keep stirring continuously and react for 15 days at a reaction temperature of 20-30°C.
[0080] S4. Collection, washing and drying of PEDOT: After the reaction is completed, use a G6 sand core funnel to filter the reaction solution to obtain a blue-black PEDOT solid. Transfer the PEDOT solid to a 500mL beaker and add 200mL of 1M hydrochloric acid. Set the ultrasonic time to 3h and the ultrasonic temperature to 80℃ to disperse the PEDOT solid in 1M hydrochloric acid. After ultrasound, filter and separate the solid product with a sand core funnel. Continue ultrasonic washing with 1M hydrochloric acid in this way, and wash for 30min each time, for a total of 6 times. Then change to distilled water, ultrasonically disperse and wash 6 times in this way, put it in a vacuum drying oven, set the drying temperature to 80℃ and dry for 48h. Put the obtained PEDOT solid product into an agate mill and grind it into fine powder to obtain PEDOT powder.
[0081] Test of prepared PEDOT powder: The test method of PEDOT powder is the same as that of Example 1. The conductivity of the PEDOT powder was measured to be 5.936×10 -3 S / cm, and the conversion rate was 52.6%.
[0082] Comparative Example 2
[0083] S1. Dissolution of EDOT: 150 mL of anhydrous ethanol and 5 g of EDOT were added to a conical flask, and a magnetic stirrer was added to the conical flask. The conical flask was then placed in a magnetic stirrer under a room temperature water bath and stirred for 30 minutes to obtain a completely dissolved EDOT ethanol solution.
[0084] S2, the dropping of ferric chloride: take 76.1g ferric chloride hexahydrate (8 times the mole number of EDOT, containing 30.4mL water) and add 49.6mL anhydrous ethanol, ultrasonic dispersion makes ferric chloride hexahydrate completely dissolved.The ferric chloride hexahydrate solution of configuration is moved to a constant pressure funnel, and the ferric chloride hexahydrate solution is slowly added dropwise to EDOT-ethanol solution, and the dropping time is not less than 2 hours.After completion of dropwise addition, 20mL anhydrous ethanol is used to clean glassware, and cleaning solution is added to the reaction solution in a lump (now there are 30.4mL water and 219.6mL anhydrous ethanol in the system).
[0085] S3. Polymerization of EDOT: Keep stirring continuously and react for 20 days at a reaction temperature of 20-30°C.
[0086] S4. Collection, washing and drying of PEDOT: After the reaction is completed, use a G6 sand core funnel to filter the reaction solution to obtain a blue-black PEDOT solid. Transfer the PEDOT solid to a 500mL beaker and add 200mL of 1M hydrochloric acid. Set the ultrasonic time to 3h and the ultrasonic temperature to 80℃ to disperse the PEDOT solid in 1M hydrochloric acid. After ultrasound, filter and separate the solid product with a sand core funnel. Continue ultrasonic washing with 1M hydrochloric acid in this way, and wash for 30min each time, for a total of 6 times. Then change to distilled water, ultrasonically disperse and wash 6 times in this way, put it in a vacuum drying oven, set the drying temperature to 80℃ and dry for 48h. Put the obtained PEDOT solid product into an agate mill and grind it into fine powder to obtain PEDOT powder.
[0087] Test of prepared PEDOT powder: The test method of PEDOT powder is the same as that of Example 1. The conductivity of the PEDOT powder was measured to be 4.360×10 -5 S / cm, and the conversion rate was 71.8%.
[0088] During the experiment, the experiment of increasing the proportion of ethanol was tested. In a short period of time, no case with a higher conversion rate could be obtained, which has no practical significance for industrial production. For example, in Comparative Example 1, when the proportion of ethanol in the solvent is greatly increased, the reaction speed may be too slow due to the inhibitory effect of ethanol on PEDOT polymerization. Even if the reaction is carried out for 15 days, a higher conversion rate cannot be achieved. At the same time, due to the long reaction time, particle agglomeration and aging are more serious, which may also lead to a sharp drop in conductivity after a long reaction. For example, in Comparative Example 2, even if the reaction time is greatly extended to 20 days at an extremely slow reaction speed, a conversion rate of 71.8% can be achieved, but the conductivity has been greatly reduced, and it also loses its industrial production value. The conductivity and conversion rate results of PEDOT powders prepared in different embodiments and comparative examples are shown in Table 1.
[0089] Table 1 Conductivity and conversion rate results of PEDOT powders prepared in different embodiments and comparative examples
[0090]
[0091]
[0092] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing high conductivity PEDOT conductive powder, characterized in that: The steps include: (1) dissolving 3,4-ethylenedioxythiophene monomer in anhydrous ethanol to obtain an EDOT solution; (2) dissolving an oxidant, ferric chloride, in water to obtain a ferric chloride solution; (3) mixing the EDOT solution and the ferric chloride solution to obtain a mixed solution, wherein the volume ratio of anhydrous ethanol to water in the mixed solution is (1-2):1; (4) The mixed solution of step (3) is continuously stirred for several days to allow a polymerization reaction to occur. After the reaction is completed, the solid-liquid separation is performed, and the obtained solid phase product is washed and dried to obtain a high-conductivity PEDOT conductive powder.
2. The preparation method according to claim 1, characterized in that The mass percentage concentration of 3,4-ethylenedioxythiophene monomer in the EDOT solution of step (1) is 3-8wt%.
3. The preparation method according to claim 1, characterized in that: The molar ratio of the 3,4-ethylenedioxythiophene monomer in step (1) to the oxidant ferric chloride in step (2) is 1:6-10.
4. The preparation method according to claim 1, characterized in that: Step (3) adding the ferric chloride solution into the EDOT solution all at once, or adding the ferric chloride solution dropwise into the EDOT solution.
5. The preparation method according to claim 1, characterized in that: Step (4) The mixed solution is continuously stirred at 20-30° C. for 3-9 days.
6. The preparation method according to claim 1, characterized in that: Step (4) The solid product obtained by solid-liquid separation is washed alternately in dilute hydrochloric acid, water and ethanol.
7. The preparation method according to claim 1, characterized in that: The drying in step (4) is performed by vacuum drying at 70-90° C. for 36-72 hours.
8. The preparation method according to claim 1, characterized in that: The conductivity of the high conductivity PEDOT conductive powder is 10 0 S / cm order of magnitude.
Citation Information
Patent Citations
Poly (3, 4-ethylenedioxythiophene) nanoparticles and preparation method thereof
CN113372538A
Conductive polymer conductor, and method for producing the same
JP2021028364A